-8p-6(6-3p)=5(p-4)-31

Simple and best practice solution for -8p-6(6-3p)=5(p-4)-31 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8p-6(6-3p)=5(p-4)-31 equation:


Simplifying
-8p + -6(6 + -3p) = 5(p + -4) + -31
-8p + (6 * -6 + -3p * -6) = 5(p + -4) + -31
-8p + (-36 + 18p) = 5(p + -4) + -31

Reorder the terms:
-36 + -8p + 18p = 5(p + -4) + -31

Combine like terms: -8p + 18p = 10p
-36 + 10p = 5(p + -4) + -31

Reorder the terms:
-36 + 10p = 5(-4 + p) + -31
-36 + 10p = (-4 * 5 + p * 5) + -31
-36 + 10p = (-20 + 5p) + -31

Reorder the terms:
-36 + 10p = -20 + -31 + 5p

Combine like terms: -20 + -31 = -51
-36 + 10p = -51 + 5p

Solving
-36 + 10p = -51 + 5p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-5p' to each side of the equation.
-36 + 10p + -5p = -51 + 5p + -5p

Combine like terms: 10p + -5p = 5p
-36 + 5p = -51 + 5p + -5p

Combine like terms: 5p + -5p = 0
-36 + 5p = -51 + 0
-36 + 5p = -51

Add '36' to each side of the equation.
-36 + 36 + 5p = -51 + 36

Combine like terms: -36 + 36 = 0
0 + 5p = -51 + 36
5p = -51 + 36

Combine like terms: -51 + 36 = -15
5p = -15

Divide each side by '5'.
p = -3

Simplifying
p = -3

See similar equations:

| -10+0.2500d=-5 | | (a+8)(a-9)=0 | | y=-x^2+14x | | (X+2)(3x^2-6x+7)= | | 116+56+v=180 | | -10+0.2500d=0 | | 9x(x+1)=270 | | 2x^3+3x^2-7=0 | | -x+6=2x-9 | | 5/7x=32 | | -6x-16=20 | | 4x^2-4=-32 | | -=q/8-19 | | An=6n+1 | | 2x^2-14x=x+27 | | 4x/3=-3/4 | | 3/4=k(16) | | f(x)=e^3x-1 | | 84+48+2s=180 | | X+x+10+2x-20=180 | | -5+23=68 | | (m+2)=168 | | (5x+6)-(2x-7)= | | 91=7(X+7) | | 6x-7=3x+4+2x+1 | | 6m+3+5-9m= | | 3(9)+y=-8 | | C-7.4=-4 | | -3(3x-1)+2(5x-4)=16 | | 3(8)+y=-8 | | ×=-5/7y=14/17 | | 64+32+h=180 |

Equations solver categories